2012
DOI: 10.1089/aid.2011.0040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vitamin D Levels Among HIV-Infected Patients in New York City

Abstract: Few studies have examined the vitamin D status in HIV-infected patients. A cross-sectional retrospective chart review of 2992 HIV-infected patients was conducted from 9/2008 to 5/2009. A total of 274 adult patients had 25-hydroxyvitamin D [25(OH)D] obtained by radioimmunoassay. None was receiving vitamin D (vitD) supplements. Vitamin D status was defined as the following: vitD deficiency (vitDd) as 25(OH)D <25 nmol/liter, vitD insufficiency (vitDi) as 25(OH)D 25-74 nmol/liter, and vitD optimal (vitDo) as 25(OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 28 publications
5
40
2
Order By: Relevance
“…In subjects on HAART, a small but significant increase in percentage of CD4 + T cells, a small decrease in viral load, and a significant decrease in the percentage of activated cytotoxic T cells (CD8 + /CD38 + /HLA-DR + ) were observed, and these results suggest a possible favorable impact on HIV status. This finding supports other studies in which vitD status was associated with higher CD4 + cell counts or reduction in RNA viral load [3,5,6,9,10]. However, this may reflect improved adherence to HAART regimen because we did not detect an improvement in CD4% or virologic control in the small number of subjects who were not on HAART.…”
Section: Resultssupporting
confidence: 90%
“…In subjects on HAART, a small but significant increase in percentage of CD4 + T cells, a small decrease in viral load, and a significant decrease in the percentage of activated cytotoxic T cells (CD8 + /CD38 + /HLA-DR + ) were observed, and these results suggest a possible favorable impact on HIV status. This finding supports other studies in which vitD status was associated with higher CD4 + cell counts or reduction in RNA viral load [3,5,6,9,10]. However, this may reflect improved adherence to HAART regimen because we did not detect an improvement in CD4% or virologic control in the small number of subjects who were not on HAART.…”
Section: Resultssupporting
confidence: 90%
“…Accordingly, a number of studies have revealed higher rates of vitamin D deficiency among HIV-positive people. [7][8][9] In recent studies, low levels of vitamin D were related to disease progression of HIV/AIDS and its complications. 10,11 The causes of this deficiency are not known but might include a defect in renal 1a-hydroxylation of 25-hydroxyvitamin D 3 mediated by proinflammatory cytokines 12 or by the intake of antiretroviral drugs.…”
mentioning
confidence: 99%
“…Of the remaining (43 papers), 30 articles reported original data with the pre-specified 25OHD cut-off values and were included in the review (Table 1). 6,[8][9][10]60 One study describing the prevalence of vitamin D deficiency in a subgroup of 21 patients with hypocalcemia and ten articles reporting 25OHD status with different cut-off levels were considered only to retrieve information about predictors of vitamin D status, 7,[48][49][50][51][52][53][54][55][56][57] and two duplicate publications were reviewed for additional data not presented in the original study. 42,58,59 Studies' characteristics…”
Section: Literature Searchmentioning
confidence: 99%
“…27,31,41 Considering other HIV-related risk factors, patchy correlations were found between HIV viral load, duration of ART, duration of HIV, plasma neopterin, or soluble tumor necrosis factor-alpha receptor I and vitamin D deficiency. 6,8,9,23,25,28,37,52,54,57 Adverse health outcomes related to vitamin D deficiency in HIV-infected patients Very few studies investigated the detrimental effects of vitamin D deficiency on health outcomes other than bone diseases in HIV+. They were primarily cross-sectional correlation analyses, and it was therefore not possible to establish a cause-effect relationship.…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
See 1 more Smart Citation